International aspects of stabilization policies : proceedings of a conference held at Williamstown, Massachusetts, June 1974 - Ando, Albert; Herring, Richard; Marston, Richard C.; Federal Reserve Bank of Boston; International Seminar in Public Economics (Boston : Available from Public Information Center, Federal Reserve Bank of Boston, 1974)
This volume contains two papers and discussions, divided into three groups. The first group are more or less theoretical in nature. The second group are based on econometric models of national economies linked together to represent an international economic system, and the behavior of these linked economies are studied by numerical, simulation analysis. The third group are special studies of stabilization problems in institutional contexts that are less familiar to American and West-European economists; less developed countries, East-Europe socialist economies and Japan
Includes bibliographical references.
osc 13/08/2018
Loans
Keywords: Economic stabilization